(untitled) (International journal of artificial intelligence, 2024)
In the lesson on technology, students are instructed to use technological equipment for practical tasks in teaching the topic in an interesting and high-quality way. The importance of enhancing students ' interests in technology, skills, creative ideas, creative thinking, the imagination of making items, and developing skills for independent work and practical assignments is highlighted.